Evaluation of digital images for identification and characterization of monoclonal immunoglobulins by immunofixation - Bender, Laura M.; Cotten, Steven W.; Fedoriw, Yuri; Willis, Monte S.; McCudden, Christopher R. (Clinical biochemistry, 2013)
High resolution digital imaging systems were recently introduced to capture and visualize serum protein electrophoresis results. In this study, we compared the performance of five, experienced interpreters using digital images and physical gels to identify and characterize monoclonal gammopathies by immunofixation. Immunofixation gels were generated using Sebia's HYDRASYS and digital images were captured with Sebia's Gelscan system. Interpreters blindly reviewed 200 consecutively obtained immunofixation results using physical gels, low resolution (LR) images, and high resolution (HR) images. Interpretations of the physical gels were significantly more sensitive (p≤0.01) than LR and HR images, and significantly more specific (p<0.001) than the LR images. Interpreters had a sensitivity of 82.0% (45.8–95.7) using the LR images and a specificity of 71.0% (47.8–91.3); using the HR images interpreters had a sensitivity of 80.4% (68.1–86.8) and specificity of 91.8% (80.3–97.8). There was 73.6% agreement between the HR digital images and the physical gel for immunoglobulin isotype characterization. Interpreters using digital images collectively missed 19 patients with monoclonal immunoglobulins that were identified using physical gels. Interpreters using digital images had significantly different performance than when using physical agarose gels. Differences were most pronounced for low concentration monoclonal gammopathies (<0.3g/dL) and for complex patterns. Between-interpreter agreement was also lower using digital images. While digital images may serve as a useful resource for retrospective analysis and review of previous results, they are not equivalent to physical gels. Additional studies are warranted to explore the clinical impact of these observed differences. [Display omitted] ► Method comparison of digital images to physical serum protein electrophoresis gels ► Physical gels were more sensitive and specific than low-resolution images. ► Physical gels were significantly more sensitive than high-resolution images. ► Physical gels and high-resolution images had equal specificity. ► The sensitivity and specificity of digital images were not suitable for routine use.